USING VIDEO REVIEW STRATEGY IN DEVELOPING STUDENTS’ WRITING SKILL - Syauqiyah Awaliyah Alfiani Nur (Institut Agama Islam Negeri (IAIN) Bone, 2022)
AbstractIt is evident that watching video activity cannot be separated from people’s life nowadays as technology becomes easier to reach. Watching video is becoming one teaching strategies for its enjoyment end enthusiasm experienced by the students. To make this activity even more advantageous in teaching and learning process, reviewing video after watching it becomes more suggested. The purpose of this study was to monitor the growth of SMA Negeri 12 Makassar's writing skills. This study's goal is to gather empirical evidence regarding the differences in writing test scores between students who received video review strategy instruction and those who did not. There are 60 students in the study's population. Class XI IPS served as the experimental group in the study, which included 21 students, and XI MIPA served as the control group, which included 39 students. This study used a quasi-experimental, non-equivalent control group design as its research methodology. Pretest and posttest were used to gather the data. It sought to ascertain whether using a video review strategy when teaching writing can improve students' writing skills.